Effects of recasts on acquisition of english plural and non-past third person singular morphemes by young ESL learners - Wan Chik, Suliana (2020)
Interactions often result in learners receiving feedback from their interlocutors. The process of engaging in interaction will greatly increase negotiation for meaning. In doing this, the learners receive feedback on their production and on grammar that they have not yet mastered. The issue of the efficacy of recast as a corrective feedback on the grammar acquisition of English second-language learners remains contentious due to the implicitness of the feedback and the complexities of the target structures. The present quasi-experimental study aims to determine the role of corrective feedback in the form of recasts on the grammar uptake of the young English as Second Language (ESL) learners. Specifically, it investigates to what extent the exposure to treatment of recasts can lead to the acquisition of the noun plural and non-past third person singular and examines whether or not recasts triggers learners’ noticing of their own erroneous utterances. The study was conducted in a primary school located in the Kinta Northern District of Perak, involving young learners of lower intermediate level of English proficiency. To test the hypothesis that recast leads to better grammar uptake, Grammaticality Judgement Task (GJT), Gap Fill Task (GFT) and Picture Description Task (PDT) were administered in the pre- and post-intervention sessions to 54 young learners. Following the intact group design, the learners were assigned to two groups: the treatment group and the control group. The treatment group received recasts in the form of teacher’s reformulation to their erroneous utterances while the control group received no error correction at all. The data were tabulated and described using descriptive statistics and analysed using ANCOVA and Independent T-tests. The oral transcription data were collected using the Recasts Episodes (RE) and the Immediate Recall (IR). Quantitative results showed that recasts as the corrective feedback have a significant effect on developing grammar acquisition (i.e noun plurals and non-past third person singular) of young ESL learners. The significant effect is seen in the GJT and GFT tests of the Immediate post-tests. The results of the study revealed higher grammar uptake for the recast group. Qualitative data from oral transcripts of the recasts episodes and immediate recall indicated that learners in the recast group have noticed the corrective function of recasts. The study also provided some empirical evidence to support the learners’ noticing of the corrective function of recasts. These results suggest that young learners receiving recasts are more likely to have noticed their errors and do self-correction and in the end resulted in repair and need repair. The learners appeared to have accurately interpreted the teacher’s intent and recasts were noticed. This study concludes that for young learners, the use of a less direct way of error correction such as recast is noticed and thus, facilitated their grammar uptake. The findings of this study shed light on the noticing of errors and self-repair by young ESL learners in their grammar uptake. This contributes insights into the SLA literature particularly on the Interaction and Noticing Hypotheses. In addition, the findings have pedagogical implications for the treatment of errors of learners in the ESL classroom.